Pengembangan Media Pembelajaran Interaktif Berbasis Lectora Inspire pada Materi Sistem Pernapasan Manusia Kelas V SD - Mahmudah, Mahmudah; Kresnadi, Hery; Pranata, Rio (YASIN, 2025)
Technological advancements have driven educators to be more creative and innovative in designing learning activities, including the development of interactive learning media to address student fatigue caused by monotonous instructional tools. This study aims to develop an interactive learning medium based on Lectora Inspire for the topic of the Human Respiratory System for Grade V elementary school students that is both feasible and effective for classroom use. The research employed a Research and Development (R&D) method using the ADDIE model, which includes the stages of Analysis, Design, Development, and Implementation, and applied a mixed-method approach. The trial subjects consisted of 23 Grade V students from SD Swasta Adicita Mulia Pontianak. Media feasibility was assessed through validation by media and content experts, as well as student responses to the developed product. The results show that the initial media design received a validity score of 0.93, categorized as “very high validity,” while the final product's design and content aspects scored 1.00, also within the “very high validity” category. Student responses reached 87.13%, categorized as “very good.” Therefore, the Lectora Inspire-based interactive learning media on the Human Respiratory System is deemed highly suitable for use and received positive feedback from students.